EVALUATION OF DIFFERENT SUTURING TECHNIQUES FOR CYSTOTOMY CLOSURE IN CANINES - I.U. Khan; M. A. Khan; A. S. Chaudhary; M. M. Ali; M. Imran; M. Ijaz; M. H. Saleem (Journal of Animal and Plant Sciences, 2013)
The experimental cystotomy was performed on 24 mongrel dogs, divided in to four groups i.e. group A, B, C and D comprising 6 dogs in each group. In group-A, cystotomy wound was closed in one layer by simple continues suturing pattern, in group-B, closure was made in two layers by simple continues and lembert suturing pattern and in group-C, cystomy incision was closed by one layer simple continues suturing pattern and two layers of inverting suturing patterns. Group-D was kept as control group. All three closure techniques were evaluated for leakage with the help of contrast radiography, ultrasonography, renal function tests and physiological parameters. Comparison of three techniques concluded that single-layer cystotomy closure is preferable in small animals because it ensure water tight closure with a good quality of wound healing and requires shorter time.
Keywords: Cystotomy; Dogs; Suturing pattern; Sonography